2020
DOI: 10.1108/jhr-05-2019-0101
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a health educational booklet

Abstract: Purpose -This study aimed to develop and validate a health education booklet (Be SAFE booklet) as a guide to improving knowledge, attitude, and practice toward drowning prevention and water safety among parents of primary school children in a local community in Selangor. Design/methodology/approach -This methodological study was conducted in two phases: the development of the content, and validation of the educational material. Booklet development involved content survey and design development. These steps con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“… 37 In addition, the use of standardised reference documents such as training manuals, booklets and leaflets has been cited as one of the approaches to increasing awareness about drowning prevention. 33 In addition, a safety training programme for commercial fishermen was developed in the USA, to prevent drowning among the fishers. 1 Not only this, health education pamphlets and leaflets have been used to teach patients in many settings about various public health-related issues.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 37 In addition, the use of standardised reference documents such as training manuals, booklets and leaflets has been cited as one of the approaches to increasing awareness about drowning prevention. 33 In addition, a safety training programme for commercial fishermen was developed in the USA, to prevent drowning among the fishers. 1 Not only this, health education pamphlets and leaflets have been used to teach patients in many settings about various public health-related issues.…”
Section: Discussionmentioning
confidence: 99%
“…A similar approach was used in Malaysia to develop and validate a health educational booklet for use by parents to prevent drowning among children. 33 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It utilizes different medium as previous studies have reported the common use of printed materials in changing the knowledge, attitude, and behaviour. 28,29 The printed materials were always relevant to be used but the current development in technology have changed some of the ways people obtain information.…”
Section: Discussionmentioning
confidence: 99%